Technology of reception of the dry cleared extract from leaves stevia. - S. A. Kedik; E. I. Jartsev; I. E. Stanishevskaja; S. V. Fedorov (Тонкие химические технологии, 2008)
The optimized method of reception of the dry cleared extract from leaves Stevia rebaudiana Bertoni with the high contents steviozid is offered. Physical and chemical properties of the dry cleared extract Stevia are investigated.